Molecular characterization of diphthamide biosynthesis protein 7 in Marsupenaeus japonicus and its role in white spot syndrome virus infection. Issue 75 (April 2018) - Wang, Ziyan; Sun, Baozhen; Zhu, Fei
Abstract: Diphthamide biosynthesis protein 7 (Dph7) is a vital protein for diphthamide biosynthesis in archaea and eukaryotes. The 1143 bp cDNA sequence of Dph7 was cloned from the gills of Marsupenaeus japonicus using RT-PCR and RACE. Data showed that Dph7 was highly expressed in the gills and digestive gland of M. japonicus . Furthermore, the expression of dph7 was induced by infection with white spot syndrome virus (WSSV). When Dph7 was knocked down, immune genes such as toll, prophenoloxidase (proPO), p53, tumor necrosis factor-α (TNF-α) and signal transducer and activator of transcription (STAT) were significantly down-regulated ( P  < 0.01) in hemocytes. First, we demonstrated that Dph7 is very important in the progression of WSSV infection and that the time of death for WSSV-infected shrimp was significantly advanced following RNAi targeting of Dph7. We also investigated the effect of Dph7 on apoptosis rate in M. japonicas and found that Dph7-dsRNA treatment caused lower levels of apoptosis in hemocytes, both in the disease-free group and the WSSV group. Knock-down of Dph7 affected the activity of both phenoloxidase (PO) and superoxide dismutase (SOD), and total hemocyte count (THC) after infection with WSSV, indicating that Dph7 plays a regulatory role in the immunological reaction of shrimp in response to WSSV infection. Thus, we conclude that Dph7 may promote the anti-WSSV immune response of shrimp by regulating apoptosis, SOD and PO activity, and can influence the progression of WSSV infection. Highlights: The 1143 bp cDNA sequence of Diphthamide biosynthesis protein 7 (Dph7) was cloned from Marsupenaeus japonicus. The Dph7 is very important for the progression of WSSV infection. The Dph7 knockdown significantly increased the mortality of WSSV-infected shrimps. The Dph7 might promote the immune response of shrimp by regulating apoptosis, PO activity and SOD activity.